Sustainable Finance and Climate Change: Wasteful but a Political Commitment Device? - Clemens Fuest; Volker Meier (Center for Economic Studies and ifo Institute (CESifo), 2022)
Promoting investment in low carbon "clean" sectors has gained popularity over the last years under the heading of sustainable finance, at the same time raising concerns about adverse welfare effects of such policies. We analyze the economic impact of subsidizing investment in "clean" industries in a stylized two-sector small open economy model. Such a reform increases gross wages, but reduces national income due to the distortion of capital. At given national emissions cap, worldwide emissions rise because imports of the high-carbon good will increase. When adapting the emissions cap, the environmental policy becomes laxer if it is dominated by income effects or by mitigating losses arising from the distortion of the allocation of capital. At the same time, the shrinking high carbon sector reduces income gains from a higher cap and thus works toward a stricter policy. Results are similar if capital in "dirty" industries is taxed. Though sustainable finance policies do seem wasteful, we provide a rationalization in a setting with irreversible investment, where a "green" government" uses such a policy to induce stricter environmental measures after a possible switch to a "conservative" government.
Keywords: F41; H23; H87; Q58; 330; climate change; global externalities; sustainable finance; small open economy; political economy